Effect of Walking Modes and Temperatures on the Robustness of Ventilation Systems in the Control of Walking-induced Disturbances - Jianlin Ren; Junjie He; Leihong Guo; Hongwan Li; Xiangfei Kong (Aerosol and Air Quality Research)
Abstract Ventilation system’s effectiveness can be affected by walking-induced disturbances. A series of experiments were performed in a chamber in this study considering the following parameter variations: four types of ventilation systems (i.e., ceiling supply and side return, ceiling supply and ceiling return, side supply and ceiling return, side supply and side return), three temperature levels (18°C, 23°C, 28°C), and three walking modes (W1, W2, W3). The test results showed that the cumulative particle exposure levels under walking modes W1, W2 and W3 were 2.04 ± 0.27, 1.72 ± 0.26 and 0.87 ± 0.12 times the exposure levels without human walking. The four ventilation systems can maintain a high stability of the indoor temperature field; however, different walking modes and ventilation systems would result in different walking-induced disturbances of the pollutant and flow fields. For the flow field, the range scale robustness (RSr) value with ventilation system was 4.0%–18.2% higher than that without ventilation system. The highest RSr value was achieved by the side supply and side return (SS) system. For the pollutant field, the RSr and time scale robustness (TSr) can be increased by 23.0%–44.0% and 11.5%–23.3% due to the ventilation systems, respectively. The RSr value of the SS system was still the largest, 18.7% larger than the smallest value. With the increase in temperature from 18°C to 28°C, the RSr and TSr of the different ventilation systems decreased by 7.7%–18.4% and 1.3%–15.7%, respectively. A ventilation system with high particle-removal efficiency may not be effective in controlling indoor disturbances. The database and method developed in this study could be beneficial for the control of human walking-induced disturbances in those settings that require a highly controlled indoor environment.